2021
DOI: 10.1021/acs.jafc.0c05997
|View full text |Cite
|
Sign up to set email alerts
|

l-Proline as a Valuable Scaffold for the Synthesis of Novel Enantiopure Neonicotinoids Analogs

Abstract: In this research, six neonicotinoid analogs derived from l-proline were synthesized, characterized, and evaluated as insecticides against Xyleborus affinis. Most of the target compounds showed good to excellent insecticidal activity. To the best of our knowledge, this is the first report dealing with the use of enantiopure l-proline to get neonicotinoids. These results highlighted the compound 9 as an excellent candidate used as the lead chiral insecticide for future development. Additionally, molecular dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In our previous work, the synthesized nitroguanidines derived from S ‐proline mimic the binding modes of control inhibitor compounds (dinotefuran), with high in vivo insecticidal effect (Figure 1A). 12 To deepen our knowledge of the mechanism of intermolecular recognition of ( R ) and ( S ) stereocenters, a molecular ensemble docking approach was performed on the nAChR structures from a 500 ns accelerated molecular dynamics simulation, using a PCA‐clustering analysis. This approach enhances molecular geometry sampling of the binding site by applying boost potential over amide dihedral angles and the system's potential energy, 34,35 while deriving more robust docking scores by using more replicas to achieve a consensus value 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, the synthesized nitroguanidines derived from S ‐proline mimic the binding modes of control inhibitor compounds (dinotefuran), with high in vivo insecticidal effect (Figure 1A). 12 To deepen our knowledge of the mechanism of intermolecular recognition of ( R ) and ( S ) stereocenters, a molecular ensemble docking approach was performed on the nAChR structures from a 500 ns accelerated molecular dynamics simulation, using a PCA‐clustering analysis. This approach enhances molecular geometry sampling of the binding site by applying boost potential over amide dihedral angles and the system's potential energy, 34,35 while deriving more robust docking scores by using more replicas to achieve a consensus value 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that nitroguanidines containing aromatic or aliphatic amines with an R configuration are substantially more bioactive than the S enantiomers (Figure 2). 12,13 Inspired by these results, we speculate that the nitroguanidine-bearing R-proline could have higher than S-proline, and we thus decided to synthesize R-proline and study its biological activity against five insects pests with agricultural activity (Galleria mellonella [caterpillar], Sitophilus zeamais, Xylosandrus morigerus, Xyleborus affinis, and Xyleborus ferrugineus). Furthermore, interactions between S-and R-proline and the nAChR were also investigated using ensembled molecular docking.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, management is currently focused on monitoring, sanitation and direct control using contact or systemic insecticides [4], and these are still subject Molecules 2021, 26, 4225 2 of 20 to ongoing investigations [5]. Indeed, efficacious and cost-effective measures are urgently needed to protect avocado from laurel wilt.…”
Section: Introductionmentioning
confidence: 99%
“…The reported neonicotinoids can be classified according to the pharmacophore as N-nitroguanidines, (imidacloprid, thiamethoxam, clothianidin, and dinotefuran), nitromethylenes (nitenpyram), and N-cyano-amidines (acetamiprid and thiacloprid) (Figure 1). To the best of our knowledge, management is currently focused on monitoring, sanitation and direct control using contact or systemic insecticides [4], and these are still subject to ongoing investigations [5]. Indeed, efficacious and cost-effective measures are urgently needed to protect avocado from laurel wilt.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that due to the presence of hydrogen-bonding donor and acceptor sites in the molecule, L-Pro has a good potential to form co-crystals, and has negligible biological toxicity [ 29 , 30 , 31 , 32 , 33 ]. In this work, we report L-Pro co-crystals of RSV and PD, namely RSV-L-Pro and PD-L-Pro, prepared under different synthetic conditions.…”
Section: Introductionmentioning
confidence: 99%